Less weight, more gain?: Pain/injury/diet issues in elite British female gymnastics - Maguire,J.; Roberts, S. (1998)
This paper examines questions of pain/injury/diet issues in elite British female gymnastics. Indepth interviews were conducted and a questionnaire administered with retired elite female gymnasts. The main themes explored focused on the extent and types of pain endured, injuries sustained and weight control strategies employed. Pain was viewed as an integral part of the sport; injuries (more or less serious) were viewed as inevitable and something to be overcome and endured; and the use of a variety of weight control strategies (some quite hazardous to health) were frequent and described in quite graphic detail. (Abstract from the British Sociological Association Annual Conference, Edingurgh, April 6-7th, 1998)